2005
DOI: 10.1038/sj.gt.3302642
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic ultrasound-mediated DNA to cell and nucleus: bioeffects revealed by confocal and atomic force microscopy

Abstract: Therapeutic ultrasound (TUS) has the potential of becoming a powerful nonviral method for the delivery of genes into cells and tissues. Understanding the mechanism by which TUS delivers genes, its bioeffects on cells and the kinetic of gene entrances to the nucleus can improve transfection efficiency and allow better control of this modality when bringing it to clinical settings. In the present study, direct evidence for the role and possible mechanism of TUS (with or without Optison) in the in vitro gene-deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 25 publications
4
107
1
Order By: Relevance
“…Although there are many reports on sonoporation [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], each experimental setting differs from one another and the reported sonoporation efficiency, which is one of the most significant information in sonoporation, varies. In order to understand the effect of the experimental settings themselves on sonoporation experiments, we first investigated the impact of the conditions of the cultured cells on sonoporation efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are many reports on sonoporation [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], each experimental setting differs from one another and the reported sonoporation efficiency, which is one of the most significant information in sonoporation, varies. In order to understand the effect of the experimental settings themselves on sonoporation experiments, we first investigated the impact of the conditions of the cultured cells on sonoporation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Some reports, including our previous reports, show only a small amount of successfully sonoporated cells accompanying a large number of non-viable cells [25,26,30,31,35]. Others report otherwise [34,38]. Although some reports have pursued the possibility of optimizing ultrasound parameters [26,35,39,40], there has been no report on investigating how the technical differences of experimental settings can impact the results.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, however, Machluf's group have reported that exposing baby hamster kidney cells to 0.16 MI 1 MHz ultrasound for 30 min in the presence of Optison MCB yielded more rhodamine-labelled plasmid in the nucleus compared with a 10 min exposure. 22,23 Whether this truly reflects a direct effect of prolonged USE upon nuclear uptake is difficult to assess as there was also more plasmid in the cytoplasm after USE for 30 min, which clearly altered the plasmid concentration gradient from cytoplasm to nucleus compared with a 10 min USE. Of note was the observation that some Optison MCB remained intact after 30 min, again consistent with, but not proof of, a role for stable cavitation in promoting UEGT.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 99%
“…26 A recent study also demonstrated that the effects of US on the cell membrane are much more profound in the presence of Optison, providing further support for the role of cavitation. 27 Thus, we have tested, for the first time, the effect of sonoporation on nonviral gene transfer to the lung. It is well established, that ultrasound is greatly attenuated when travelling through air.…”
Section: Introductionmentioning
confidence: 99%